Endangered species - Ricorico (Gloucester, Mass. : Rockport; Hove RotoVision [distributor], 2010)
A collection of usable artwork for designers and artists, 'Endangered Species' features 100 thematic illustrations in popular categories to use freely and to manipulate or enhance and supplement existing works.
Keywords: Endangered species in art; Decoration and ornament -- Animals forms